Effects of dietary selenium on immune function of spleen in mice. (February 2022) - Zhang, Xin; Zhang, Liangliang; Xia, Kaide; Dai, Jie; Huang, Jiangtao; Wang, Yun; Zhu, Guiming; Hu, Zuquan; Zeng, Zhu; Jia, Yi
Graphical abstract: Highlights: Low and high selenium affected the secretion of cytokines and impaired the immune function of spleen. Effects of dietary selenium on the proteome of spleen was revealed for the first time. Some important proteins related to immune cell function and immune diseases were affected by dietary selenium. Abstract: The effects of selenium on serum cytokines, immune cell composition and spleen proteome in mice are still unclear. In this study, male mice were fed with selenium-containing diets for eight weeks, and serum cytokines were assayed using Luminex liquid suspension chip. The spleen was obtained for histological morphology, immunohistochemistry and proteome sequencing. The results indicated that the spleen index and histological structure of the spleen were reduced and damaged with low and high selenium. Serum cytokines were regulated by selenium. Additionally, compared with medium selenium, there were 180 and 189 differential proteins with high and low selenium, respectively. The differential proteins were mainly associated with metabolic processes, regulation of response to oxidative stress, cell maturation and differentiation, cytokines and receptor binding, and were verified using Western blotting. In conclusion, it was suggested that low and high selenium affected the secretion of cytokines and impaired the immune function of the spleen.